Sikap Terhadap Tradisi Barat: Telaah Eurosentrisme Max Weber: Analisis Oksidentalisme Hassan Hanafi - Haryono, Satrio Dwi (Jurusan Aqidah dan Filsafat Islam Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2022)
Sociology is a science that studies human-human relations. Sociology emerged later than other disciplines. Max Weber, a western sociologist who studies the eastern world as the object of his study, is considered to have a lot of ethnocentric content, namely Eurocentric. This has implications for the creation of a reflection of Europe, namely the east, which Weber describes eloquently. Although at first Weber tried to explain the process of change in Western Europe, but oddly enough, he studied the east as the other or the other of Europe. As a methodological tool, the author uses library research. In this study, the author uses Hassan Hanafi's Occidentalism approach to challenge the Eurocentrism narrative offered by Max Weber. The results of this study indicate that Eurocentrism is attributed to Europe which in the course of history will lead to major humanitarian problems that Weber did not calculate such as colonialism and imperialism and requires a full lawsuit against the discourse through Occidentalism.